Participation of psychologists in Istanbul Protocol based physical examinations: an applied perspective - Weishut, Daniel (Torture Journal, 2022)
Being invited to do an evaluation of another asylum seeker, this time one from Turkey, a question kept coming to my mind. The question is as follows: Wouldn’t it be important for mental health professionals to take part in Istanbul Protocol (IP) based physical examinations? The intent is not to do the physical examination, but to be present, observe, ask questions when appropriate, and witness, with the consent of the client. The article elaborates on this question, while both sharing my perspective as a clinical psychologist and referring to relevant literature.